A comparative study on dietary diversity and nutritional adequacy between dementia patients and healthy individuals in Kolkata, West Bengal - Dutta, Soumam; Roy, Sohini; Roy, Sanchari; Manna, Ananta (International Journal Of Community Medicine And Public Health, 2021)
Background: Dementia is a chronic condition characterised by a progressive loss of memory, thinking and behaviour. Several studies indicate that nutritional status as well as dietary intake of many patients having dementia are not adequate. Malnutrition is a common problem faced by these patients. Dietary diversity is an important indicator of dietary quality. It is a well-known factor which influences the nutritional status of individuals. The current study aims to compare the dietary diversity and nutritional adequacy of dementia patients and healthy individuals. Methods: 60 dementia patients and 60 controls were recruited as per the study protocol. 24-hour dietary intake was recorded. Dietary diversity was assessed in terms of Food Variety Score (FVS), Dietary Diversity Score (DDS) and Dietary Serving Score (DSS). Additionally, Nutrient Adequacy Ratio (NAR) was calculated for energy and 15 nutrients (Carbohydrate, Protein, Visible Fat, Thiamine, Riboflavin, Niacin, Pyridoxine, Vitamin B12, Folic Acid, Vitamin A, Vitamin C, Calcium, Magnesium, Iron and Zinc). Mean Adequacy Ratio (MAR) of the diet was also calculated. Results: The mean values of FVS (7.2±2 versus 8.1±1.4), DDS (4.1±1 versus 4.8±0.5), DSS (10.8±2 versus 14.2±1.2) were significantly lower in the dementia group as compared to the healthy subjects. The NAR and MAR values were also lower in the dementia group except for vitamin B12. But the intake of vitamin B12 was lower than the Estimated Average Requirement. Conclusions: In the present study it was observed that the diversity and nutritional adequacy of the diets consumed by dementia patients were poor as compared to the healthy individuals. Necessary measures should be taken to improve the dietary quality of dementia patients.